Credibility and Independence of Evaluation in UNDP: A Response to David Lempert - Juha I. Uitto (The Evaluation Center at Western Michigan University, 2010)
The paper contains a response to the article by David Lempert on 'Why Government and Non-governmental Policies and Projects Fail Despite Evaluation' (JMDE, Vol. 6, No. 13, 2010). The paper focuses on the role of the evaluation function in public organizations, using the example of the United Nations Development Programme. It makes broader observations regarding the independence and credibility of evaluation. Finally, the role of evaluation in oversight is discussed.